Involvement of Digital Platforms in the Process of Payment of Accommodation Tax in Slovakia – Theory vs. Reality - Anna Vartašová; Karolína Červená (Acta Universitatis Lodziensis Folia Iuridica)
Digitization in the field of taxation represents one of the possible ways of improving the quality and increasing the transparency of this process. We can conclude that, in Slovakia, the potential of digitization for streamlining tax processes as well as increasing taxpayers’ satisfaction is indicated. One of the elements of the tax system where such an aspect is identified is the accommodation tax, where the recent amendment of the Local Taxes Act of 2021 made digital platforms’ operators directly involved in the process of collecting and paying this tax. In this paper, the authors present partial results of their primary research aimed at a critical evaluation of the current state of the transfer of the obligation to collect accommodation tax from the accommodation provider to digital platform operators in the Slovak Republic. The authors came to the conclusion that despite the effort of the legislator to solve a specific aspect of the activity of digital platforms (in relation to the payment of accommodation tax), the amendment of the legislation did not bring about the desired change in application practice and the new legal regulation is not actually applied in practice. In our opinion, the reason for this state of affairs is, on the one hand, the ambiguous wording of the legislative text, from which the actual transfer of the tax collection obligation to the platform operators is questionable, and, on the other hand, only a minimal reduction of the administrative burden of accommodation providers when applying this new regime.